Influences of age-related changes in mesenchymal stem cells on macrophages during in-vitro culture - Yuan Yin; Rui-Xin Wu; Xiao-Tao He; Xin-Yue Xu; Jia Wang; Fa-Ming Chen (Stem Cell Research & Therapy, 2017)
Abstract Background Mesenchymal stem cells (MSCs) have been widely used in cytotherapy and tissue engineering due to their immunosuppressive ability and regenerative potential. Recently, the immunomodulatory influence of MSCs has been gaining increasing attention because their functional roles in modulating immune responses likely have high clinical significance. Methods In this study, we investigated the influence of MSCs on macrophages (Mφs) in in-vitro cell culture systems. Given evidence that aged MSCs are functionally compromised, bone marrow-derived MSCs (BMSCs) isolated from both young and aged mice (YMSCs and AMSCs) were evaluated and contrasted. Results We found that YMSCs exhibited greater proliferative and osteo-differentiation potential compared to AMSCs. When cocultured with RAW264.7 cells (an Mφ cell line), both YMSCs and AMSCs coaxed polarization of Mφs toward an M2 phenotype and induced secretion of anti-inflammatory and immunomodulatory cytokines. Compared to AMSCs, YMSCs exhibited a more potent immunomodulatory effect. While Mφs cocultured with either YMSCs or AMSCs displayed similar phagocytic ability, AMSC coculture was found to enhance Mφ migration in Transwell systems. When BMSCs were prestimulated with interferon gamma before coculture with RAW264.7 cells, their regulatory effects on Mφs appeared to be modified. Here, compared to stimulated AMSCs, stimulated YMSCs also exhibited enhanced cellular influence on cocultured RAW264.7 cells. Conclusions Our data suggest that BMSCs exert an age-related regulatory effect on Mφs with respect to their phenotype and functions but an optimized stimulation to enhance MSC immunomodulation is in need of further investigation.